Analisis VECM Terhadap Kausalitas IPM Dan Pertumbuhan Ekonomi Di Kalimantan Tengah - Nurafny Indrawati; Lidiae Lidiae; Dahlia Dahlia; Sumarianto Sumarianto; Maria Vivi Arindha; Jepri Jepri; Ahmad Suhairi; Parista Kristina; Fernando Mirip; Dicky Perwira Ompusunggu (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Indicators of the success of a region's development performance can be measured based on two variables, namely the Human Development Index and the Economic Growth Index. This research aims to analyze the causality of HDI and economic growth in Central Kalimantan in 2013-2022. The approach used for this research is the Vector Error Correction Model (VECM). The research results state that the Human Development Index (HDI) and economic growth have a significant influence on each other. There is a causal relationship between HDI and economic growth, but not vice versa, which indicates a unidirectional causality relationship. Moreover, there is no long-term relationship between the two, but both have short-term effects. This research can increase understanding of the components that influence Central Kalimantan's economic growth and can serve as a reference for subsequent research. The results of this study can be used by the government and society to formulate more effective economic development policies and strategies in Central Kalimantan.